Experimental investigation of brick masonry roofing system - Sinha, S. N.; Dogra, V. K. (Journal of Structural Engineering, 2025)
Shallow spherical domes have been used successfully to cover large circular areas in many ancient buildings. Study of ancient temples, palaces, forts and churches reveals that square and rectangular areas have also been covered with brick / stone masonry in the past. This was done by filling corners gradually, thus converting square area into a circular area which could be easily covered as spherical dome. This paper describes experimental investigation of a brick masonry square slab, 3.886 m x 3.886 m centre to centre, constructed with conventional clay bricks and cement sand mortar without use of shuttering. Brick masonry slab is provided curvature in both directions with very small rise at the centre so that the curved top surface could be leveled by filling with suitable material, for further use as upper floors. This brick masonry slab was tested by applying uniformly distributed load on its surface with sand bags. The slab sustained load of 14.29 kN/m² without collapse, in comparison to actual load of 6.87 kN/m² in residential areas. Deflections at different locations in the slab were also found to be within the permissible limits and rebound on removal of load was satisfactory. Absence of any visible sign of failure in slab indicated that the meridional and hoop stresses in brick masonry slab were well within the permissible limits during the entire process of loading and unloading. Thus, it is concluded that such brick masonry slabs of reasonable spans are safe for residential use.